Development and Implementation of an Ultraviolet-Dye-Based Qualification Procedure for Hand Washing and Disinfection to Improve Quality Assurance of Pharmacy Preparations and Compounding, Especially in Cleanrooms: A Pilot Study - Catharina W. J. Knol; Paul H. Stob; Herman J. Woerdenbag (MDPI AG, 2024)
Even though, nowadays, most medicines are manufactured industrially, patients may have medical needs that can only be met by a tailor-made approach. This requires the availability of pharmacy preparations made under Good Manufacturing Practice (GMP) conditions. An efficient hand hygiene practice is essential herewith, especially if sterile products that are prepared in a cleanroom are concerned. The effectiveness of hand washing and hand disinfection procedures greatly relies on adequate training. We carried out an observational cross-sectional pilot study aimed at optimizing hand hygiene training with objective and measurable quality assessments using an ultraviolet (UV) dye. Practical acceptance criteria for qualifying personnel through this method were set and evaluated. In total, 25 GMP-qualified cleanroom operators washed and disinfected their hands with UV dye hand wash lotion and UV dye hand alcohol, respectively. To obtain a proof-of-concept, the results were judged based on adherence to the WHO six-step protocol and associated acceptance criteria. Commonly missed areas were brought to light, and the influence of procedure duration was investigated. UV-dye-based assessments appeared to be more valuable in hand disinfection than in hand washing. In both procedures, the back of the hands and the thumbs were frequently missed. This underpins the need for enhanced and repeated education on hand washing and disinfection. Additionally, a dry skin gave rise to extra cleaning challenges. From this pharmacy practice pilot study with a focus on pharmaceutical product care, it may be concluded that the application of UV-dye-based assessments offers valuable insights for pharmacists to optimize hand hygiene, thereby increasing the safety of tailor-made medicines and on-site preparations.